Novel strategies for nanovaccine application in breast cancer treatment - Liu, Huan; Ma, Ning (Frontiers in Pharmacology, 2025)
Breast cancer (BC), as the most common malignant tumor among women globally, faces numerous challenges in treatment. Currently, although the combination of surgical resection with various treatment modalities such as chemotherapy, radiotherapy, and immunotherapy can improve patient survival rates, most BC patients are diagnosed at an advanced stage. Additionally, traditional small-molecule targeted anticancer drugs used during chemotherapy suffer from issues such as low target selectivity and frequent occurrence of acquired resistance, leading to suboptimal therapeutic outcomes. In recent years, tumor immunotherapy has achieved significant progress. Notably, cancer vaccines, as a strategy within tumor immunotherapy, represent a promising therapeutic approach by inducing tumor-specific immune responses. However, cancer vaccines also face several limitations, such as the strong systemic toxicity of immune adjuvants and the low immunogenicity of tumor antigens. An ideal cancer vaccine should sufficiently stimulate the body to generate a potent tumor-specific immune response while exhibiting low side effects. With innovations in nanotechnology within the medical field, nanotechnology can help overcome the limitations of traditional vaccines in the realm of vaccination. This review summarizes various nanomaterial carriers applied in the manufacturing of nanovaccines. These nanomaterials exhibit excellent biocompatibility, adjuvant activity, and immunogenicity. Furthermore, we discuss and summarize preparation strategies to enhance antitumor immune efficacy, including the use of tumor neoantigens to improve antigen presentation, the application of tumor cell membrane-based biomimetic nanotechnology to promote targeted delivery of nanovaccines, nanovaccine delivery platforms targeting the tumor microenvironment (TME), and novel strategies for combined application with nanovaccines. As an emerging strategy for BC immunotherapy, nanovaccines offer a novel approach to address the challenges of BC treatment and post-surgical recurrence by enabling precise delivery of tumor antigens, efficient activation of immune responses, and remodeling of the tumor microenvironment.